TM1-2 Diffuse low grade glioma after the 2016 WHO update, seizure characteristics, imaging correlates and outcomes. Issue 3 (14th February 2019) - Roberts, M; Hayhurst, C; Shires, J; Northmore, T
Abstract : Objectives: Seizures are a common presenting symptom in patients with low grade glioma (LGG). Exact mechanisms of epileptogenesis are unknown and the influence of radiological and histological characteristics are not well studied, particularly after the 2016 WHO reclassification of gliomas. We aimed to define predictors of seizure development and outcome in patients with LGG. Design: Retrospective single institution case series. Subjects: 63 patients who underwent resection of supratentorial LGG in a single institution, 45 presented with seizures. Methods: Retrospective analysis of patient records to assess seizure outcome and other demographics including radiological variables, tumour characteristics, type of surgery and histology based on the 2016 WHO update. Results: After surgery, 33 patients (73%) who presented with seizures were Engel class I at median follow up of 43 months. Complete and near total resection were associated with improved Engel class compared to subtotal resection. Awake craniotomy gave improved seizure outcomes compared to under general anaesthesia (84% vs 65%). Molecular genetics did not predict seizure outcome. Updated histology did not predict seizures at diagnosis, only tumour heterogeneousity on initial MRI (p=0.043). Tumour volume at presentation impacted EOR but not seizure outcome. Conclusions: Seizure outcome is directly related to EOR. Tumour histology based on molecular genetics did not predict seizure development or outcome. Use of awake craniotomy results in greater EOR and improved Engel class.